2021
DOI: 10.1093/ajcn/nqab066
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low serum zinc concentrations in Indian children and adolescents: findings from the Comprehensive National Nutrition Survey 2016–18

Abstract: Background It is thought that there is a high risk of zinc deficiency in India, but there are no representative national estimates. Objectives We aimed to evaluate the national and state-level prevalence of low serum zinc concentrations (SZCs) in Indian children from the nationally representative Comprehensive National Nutrition Survey. Methods Prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Some of the studies have reported that peer influences, availability and access to ready to eat energy-dense food, nutrient poor convenience foods at homes, schools, and urban neighbourhoods and eye-catching repeated commercials on fast foods in mass media, perhaps are the undesirable influencers on food habits of children and adolescents in urban India. ( 22 ) The above factors were not studied but likely to exist and may have contributed to children developing unhealthy food habits leading to micronutrient deficiencies. Further studies are needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies have reported that peer influences, availability and access to ready to eat energy-dense food, nutrient poor convenience foods at homes, schools, and urban neighbourhoods and eye-catching repeated commercials on fast foods in mass media, perhaps are the undesirable influencers on food habits of children and adolescents in urban India. ( 22 ) The above factors were not studied but likely to exist and may have contributed to children developing unhealthy food habits leading to micronutrient deficiencies. Further studies are needed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Low serum zinc in schoolchildren (6-15 yr) has been reported to be more than 83 per cent in our neighbouring country Nepal 24 , and in Cameroon 25 , the prevalence of low serum zinc is reported to be 82 per cent in women (15-49 yr). Comprehensive National Nutrition Survey (CNNS) 2016-18 provides estimates of serum zinc deficiency in adolescents 6 . As per the survey report, nearly 32 per cent of the adolescents in India and nearly 20 per cent adolescents in MP were found to have low serum zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is another crucial stage in growth and development, and therefore, zinc deficiency could be detrimental in such stage of life. During adolescence, higher prevalence of inadequate zinc intake 4 and low serum zinc (ranging from 30 to 98%) have been reported 5 , 6 . Studies among tribal adolescent and non-adolescent populations have also reported higher prevalence 7 , 8 .…”
mentioning
confidence: 99%
“…The data for this analysis were obtained from the Comprehensive National Nutrition Survey (CNNS) ( 6 ) a cross-sectional, nationally representative survey of Indian children and adolescents, which was conducted in 30 states of India between 2016 and 2018, under the aegis of the Ministry of Health and Family Welfare, Government of India, in collaboration with United Nations International Children's Emergency Fund (UNICEF), India and the Population Council, Delhi, India. The survey design and sampling methodology are already published elsewhere ( 6 – 8 ). Briefly, a multi-stage, population proportional to size cluster sampling was done to enroll preschool (1–4 years), school age (5–9 years) children, and adolescents (10–19 years), to adequately represent the national, state, male-female, and urban-rural population.…”
Section: Methodsmentioning
confidence: 99%